Distribution. From W Europe E in Cricetidae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Distribution. From W Europe E to the River Yenisei in Siberia, including Belgium, Netherlands, France, Germany, Poland, Czech Republic, E Austria, Slovakia, Hungary, Slovenia, N Croatia, N Serbia, Romania, N Bulgaria, Moldova, S Belarus, Ukraine, Russia, Kazakhstan, and NW China (Xinjiang). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 286, DOI: 10.5281/zenodo.6707142 ...